2008
DOI: 10.1007/s11743-008-1103-5
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Aroma Chemicals on Cotton Fabric in Different Aqueous Environments

Abstract: Surfactants enhance adsorption of an aroma chemical on cotton fiber. Strong hydrophobic and electrostatic interactions between surfactant and fiber substrate result in higher adsorption of surfactant/aroma chemical aggregates than for the aroma chemical alone, with higher adsorption for cationic systems than for anionic systems. Adsorption is attributed to solution physical entrapment, hydrophobic interaction, dispersion forces, and interaction with surfactant molecules adsorbed on fiber. Log P and water solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The protected and therefore more hydrophobic pro-fragrance 2 gave the best results in the soener release test. This observation is also supported by earlier studies for apolar molecules 24 and polymers 13 where the deposition of hydrophobic compounds is more efficient than the one for hydrophilic ones. Taking in account the release data from the direct deposition, profragrance 3 shows the highest release aer three days, due to the more hydrophilic nature of the backbone molecule.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The protected and therefore more hydrophobic pro-fragrance 2 gave the best results in the soener release test. This observation is also supported by earlier studies for apolar molecules 24 and polymers 13 where the deposition of hydrophobic compounds is more efficient than the one for hydrophilic ones. Taking in account the release data from the direct deposition, profragrance 3 shows the highest release aer three days, due to the more hydrophilic nature of the backbone molecule.…”
Section: Discussionsupporting
confidence: 85%
“…16,32 Another well-known effect of the surfactant, besides acting as a soener which smoothens the fabric, is its ability to facilitate the deposition of nonpolar molecules onto the cotton surface. 24 Thus, cotton sheets were washed with aqueous mixtures comprising the surfactant and either of the profragrances, wringing the wet tissue to a pre-dened weight, and drying the samples for three days in a dark cupboard (Fig. 1).…”
Section: Dynamic Headspace Analysis Of D-damascone Release From Washe...mentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of both ionic and non-ionic surfactants onto solid cellulosic surfaces has been extensively studied over the years using a wide variety of experimental techniques. [4][5][6][7][8][9][10][11][12][13][14][15] Factors such as the structure of the surfactant, the structural groups on the solid surface, and the chemical and physical properties of the bulk solution have been found to affect surfactant adsorption on cellulosic surfaces. Early research by Weatherburn and Bayley 16 and Ginn et al 17 has shown that ionic surfactants adsorb more readily than non-ionic compounds, with cationic surfactants having the highest rate of adsorption on cellulosic surfaces.…”
mentioning
confidence: 99%
“…Many review articles were studied the dielectric dynamic spectroscopy of the pure polysaccharides like cellulose and their derivatives [13][14][15][16][17][18][19][20][21][22]. Dielectric relaxation separates different molecular groups of a repeating unit of a polymer with respect to the rate of its orientation dynamics were studied [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%